Ornithodoros puertoricensis (Ixodida: Argasidae) Associated With Domestic Fowl in Rural Dwellings From Córdoba Department, Caribbean Colombia - López, Yesica; Robayo-Sánchez, Laura Natalia; Muñoz-Leal, Sebastián; Aleman, Ader; Arroyave, Esteban; Ramírez-Hernández, Alejandro; Cortés-Vecino, Jesús Alfredo; Mattar, Salim; Faccini-Martínez, Álvaro A. (Frontiers in Veterinary Science, 2021)
Ticks of genus Ornithodoros are nidicolous parasites associated with a wide array of vertebrates. In humans, their bites cause hypersensitivity reactions and are capable to transmit pathogens of health concern. In the department of Córdoba, Caribbean region of Colombia, the first report of an Ornithodoros soft tick was made in 1980 by Betancourt, who described the collection of Ornithodoros talaje in human dwellings. Nevertheless, current the records of O. talaje made in South America have been questioned and likely correspond to misidentifications with morphologically similar species. Between October and December of 2020, we visited rural areas of four localities from three municipalities within the department of Córdoba: Cuero Curtido and Severá (municipality of Cereté), El Espanto (municipality of Planeta Rica), and Arroyo Negro (municipality of San Carlos). Search for soft ticks was performed in 46 human domiciles and peridomiciliary areas. We searched in areas frequented by domestic animals, inspecting cracks in the walls and fowl nests. Infestation by soft ticks was found in 13% (6/46) of visited houses. Overall, 215 ticks were collected (26 larvae, 144 nymphs and 45 adults) from nests of domestic birds or in the adjacent walls. Larvae, nymphs and adults were morphologically identified as Ornithodoros puertoricensis. Molecular identification of ticks was confirmed by sequencing the tick mitochondrial 16S gene of adults, pools of nymphs and larvae. Pairwise comparisons showed a 99% of identity with O. puertoricensis from Panama. This study reports for the first time O. puertoricensis associated with domestic fowl in rural dwellings in Colombia, and expands the geographical distribution of this tick species towards the Córdoba department. Importantly, local people described exposure to tick bites while sleeping in infested houses; therefore, the transmission of soft tick-borne pathogens is now of concern in the region.